PEMBERDAYAAN MASYARAKAT DENGAN DIFERENSASI PRODUK MAKANAN DAN MINUMAN DARI DAUN KELOR GUNA MENGEMBANGKAN KREATIVITAS MASYARAKAT - Wuryanti, Lestari; Lukman, Iing; Nursari, Ayu; Lingga Ramadan, Arya Rama; Fitri, Cut; Febrianti, Dian; Laurenza, Dinda (Program Studi Manajemen Fakultas Ekonomi dan Manajemen Universitas Malahayati, 2022)
Many Indonesian people do not know that Moringa leaves can be used and used as an innovative management of food and beverage products that are beneficial to the body. Seeing the potential produced from Moringa leaf plants as a product management material, it can be used as an effort to increase the income of local communities through community creativity development programs. With this program activity, it is hoped that it can improve the skills of the people of Srengsem Village, Panjang District, Bandar Lampung. The purpose of this Proker, apart from increasing community creativity, also introduces the basics of MSME and provides product innovation to the people of the Srengsem area, Panjang District, Bandar Lampung. The importance of MSME is the motivation for holding product innovation introduction activities through our work program, namely the development of community creativity towards Moringa leaves as food and beverage product innovations. Micro, Small and Medium Enterprises (MSME) are businesses run by individuals, households, or small business entities. The writing method used in collecting data is by using direct observation in Srengsem village, Panjang district, Bandar Lampung.